2009
DOI: 10.1007/s00419-009-0336-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on a vertical plate with variable viscosity and thermal conductivity

Abstract: Free convection over an isothermal vertical plate immersed in a fluid with variable viscosity and thermal conductivity is studied in this paper. We consider the two-dimensional, laminar and unsteady boundary layer equations. Using the appropriate variables, the basic governing equations are transformed to non-dimensional governing equations. These equations are then solved numerically using a very efficient implicit finite difference scheme known as Crank-Nicolson scheme. The fluid considered in this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…1, 2). The effect of b k on the flow was the similar result observed by Attia (1999) and Palani and Kim (2010).…”
Section: Resultssupporting
confidence: 83%
“…1, 2). The effect of b k on the flow was the similar result observed by Attia (1999) and Palani and Kim (2010).…”
Section: Resultssupporting
confidence: 83%
“…Molla et al (2009) considered the natural convection laminar flow with temperature dependent viscosity and thermal conductivity along a vertical wavy surface. Numerical study on a vertical plate with variable viscosity and thermal conductivity has been reported by Palani and Kim (2010). The Crank-Nicolson type of finite difference scheme was used in his work.…”
Section: Introductionmentioning
confidence: 99%
“…Nasrin and Alim [23] investigated magnetohydrodynamic free convection flow along a vertical flat plate with thermal conductivity and viscosity depending on temperature. Numerical study on a vertical plate with variable viscosity and thermal conductivity has investigated by Palani and Kim [24]. Aldoss et al [25] [28] investigated entropy generation during fluid flow in a channel under the effect of transverse magnetic field.…”
Section: Isrn Mechanical Engineeringmentioning
confidence: 99%